A network pharmacology approach to discover active compounds and action mechanisms of San-Cao Granule for treatment of liver fibrosis - Wei S; Niu M; Wang J; Wang J; Su H; Luo S; Zhang X; Guo Y; Liu L; Liu F; Zhao Q; Chen H; et al. (Dove Medical Press, 2016)
Shizhang Wei,1,2 Ming Niu,3 Jian Wang,2 Jiabo Wang,3 Haibin Su,4 Shengqiang Luo,5 Xiaomei Zhang,2,6 Yanlei Guo,6 Liping Liu,1 Fengqun Liu,1 Qingguo Zhao,1 Hongge Chen,1 Xiaohe Xiao,3 Pan Zhao,4,7 Yanling Zhao1,2 1Department of Pharmacy, 302 Hospital of People’s Liberation Army, Beijing, People’s Republic of China; 2Pharmacy College, Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China; 3China Military Institute of Chinese Medicine, 302 Hospital of People’s Liberation Army, Beijing, People’s Republic of China; 4Liver Failure Therapy and Research Center, 302 Hospital of People’s Liberation Army, Beijing, People’s Republic of China; 5Department of Integrative Medical Center, 302 Hospital of People’s Liberation Army, Beijing, People’s Republic of China; 6Chong Qing Academy of Chinese Traditional Materia Medica, Key Laboratory of Chongqing TCM Resources, Chongqing, People’s Republic of China; 7Clinical Trial Center, 302 Hospital of People’s Liberation Army, Beijing, People’s Republic of China Ethnopharmacological relevance: San-Cao Granule (SCG) has been used in patients with liver fibrosis for many years and has shown good effect. However, its mechanism of therapeutic action is not clear because of its complex chemical system. The purpose of our study is to establish a comprehensive and systemic method that can predict the mechanism of action of SCG in antihepatic fibrosis.Materials and methods: In this study, a “compound–target–disease” network was constructed by combining the SCG-specific and liver fibrosis–specific target proteins with protein–protein interactions, and network pharmacology was used to screen out the underlying targets and mechanisms of SCG for treatment of liver fibrosis. Then, some key molecules of the enriched pathway were chosen to verify the effects of SCG on liver fibrosis induced by thioacetamide (TAA).Results: This systematic approach had successfully revealed that 16 targets related to 11 SCG compounds were closely associated with liver fibrosis therapy. The pathway-enrichment analysis of them showed that the TGF-β1/Smad signaling pathway is relatively important. Animal experiments also proved that SCG could significantly ameliorate liver fibrosis by inhibiting the TGF-β1/Smad pathway.Conclusion: SCG could alleviate liver fibrosis through the molecular mechanisms predicted by network pharmacology. Furthermore, network pharmacology could provide deep insight into the pharmacological mechanisms of Chinese herbal formulas. Keywords: San-Cao Granule, network pharmacology, liver fibrosis, TAA